ANALISIS NILAI WAKTU KENDARAAN PRIBADI DI KABUPATEN ACEH BARAT - Ferdiansyah Novriza (VOCATECH: Vocational Education and Technology Journal, 2022)
The value of travel time is a necessity that is needed by travelers. Efficient time value will make a lot of cost savings to be incurred. Sisingamangaraja Street in Johan Pahlawan District, West Aceh Regency is one of the areas that is currently very developed. This is because this area is a place for offices, education, trade and housing for residents. The density of this area often causes traffic problems such as congestion so that accidents often occur. The purpose of this study was to determine the value of time spent by travelers using private vehicles (cars motorbikes). The method used in this research is descriptive quantitative method, by distributing questionnaires directly to private vehicle users. Data from the questionnaire will be analyzed by using multiple linear regression method with SPSS software to get equation of time value for cars and motorcycles. The results obtained from the data analysis show that there are several variables that affect the value of travel time, including: the amount of income (X3), type of work (X2), travel time (X5) and travel costs (X8). The regressions obtained for each vehicle are: cars, Y = 272,320 – 2,170 X2 + 1,113 X3 – 46,770 X5 + 112,113 X8 and motorcycles, Y = 20,289 – 3,429 X2 + 3,153 X3 – 36,475 X5 + 78,129 X8. From these equations it can be concluded that the time value of a car is Rp. 35,021.28/hour and the value of travel time for a motorcycle is Rp. 14,508.66/hour.Keywords:Keyword: Time Value; Private Vehicle; Multiple Linear Analysis.